Integrals involving generalized hypergeometric and Kampé de Fériet function - Ana Isolina Prieto; Leda Galué (Revista Técnica de la Facultad de Ingeniería, 2011)
Integrals involving hypergeometric functions have diverse applications in analysis, statistics, physics and engineering. In this work we evaluate integrals involving the generalized hypergeometric function and the Kampé de Fériet function. The results obtained are general and include some known integrals as particular cases.